1995
DOI: 10.1073/pnas.92.11.4887
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q reductase from liver plasma membrane: purification and role in trans-plasma-membrane electron transport.

Abstract: A specific requirement for coenzyme Q in the maintenance of trans-plasma-membrane redox activity is demonstrated. Extraction of coenzyme Q from membranes resulted in inhibition of NADH-ascorbate free radical reductase (trans electron transport), and addition of coenzyme Qlo restored the activity. NADH-cytochrome c oxidoreductase (cis electron transport) did not respond to the coenzyme Q status. Quinone analogs inhibited trans-plasma-membrane redox activity, and the inhibition was reversed by coenzyme Q. A 34-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
99
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(100 citation statements)
references
References 12 publications
1
99
0
Order By: Relevance
“…The addition of either ferricyanide or exogenous Q to growth media can replace the requirement of °cells for pyruvate (43)(44)(45). The exogenous Q is known to function in a trans-plasma membrane electron transport system, where intracellular NADH is oxidized and electrons are transferred across the plasma membrane to a wide variety of extracellular acceptors, including ferricyanide (46,47). In fact, this trans-plasma membrane electron transport system is up-regulated in °cells (43), and there is a concomitant increase in the level of Q at the plasma membrane (48).…”
Section: Discussionmentioning
confidence: 99%
“…The addition of either ferricyanide or exogenous Q to growth media can replace the requirement of °cells for pyruvate (43)(44)(45). The exogenous Q is known to function in a trans-plasma membrane electron transport system, where intracellular NADH is oxidized and electrons are transferred across the plasma membrane to a wide variety of extracellular acceptors, including ferricyanide (46,47). In fact, this trans-plasma membrane electron transport system is up-regulated in °cells (43), and there is a concomitant increase in the level of Q at the plasma membrane (48).…”
Section: Discussionmentioning
confidence: 99%
“…In previous investigations, DCIP and FeCN have been used interchangeably (Larm et al 1994;Zurbriggen and Dreyer 1994;Vaillant et al 1996), and studies that showed FeCN reduction is ubiquinone-dependent did not measure DCIP reduction (Sun et al 1992;Villalba et al 1995). Biochemical analyses of purified plasma membranes have identified multiple PMOR activities in a homogeneous neuroblastoma cell line (Zurbriggen and Dreyer 1994).…”
Section: Discussionmentioning
confidence: 99%
“…As a whole, both CoQ and its reductases ( Figure 1) constitute a transplasma membrane antioxidant redox system responsible of the above described functions. [51][52][53] The aforementioned antioxidants are maintained in their reduced forms at the plasma membrane by different CoQdependent reductases, NADH-dependent cytochrome b 5 reductase 53 and NAD(P)H:quinone-oxidoreductase-1 (NQO1). 55 Different dietary modifications can modulate these enzyme activities to protect the plasma membrane.…”
Section: Cr Increases Coenzyme Q-dependent Reductases In Plasma Membrmentioning
confidence: 99%